Study of antioxidant potential of malotilate in ethanol induced hepatic dysfunction in Sprague Dawley rats - Borole, Kanchan Dnyanesh; Swami, Ravi; Padalkar, Pradnya Hemant (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Alcoholic liver disease (ALD) is one of the major causes of mortality and morbidity worldwide. Objective of the study was to elicit a preventive mechanism of malotilate, a reported potent hepatoprotective agent, against ethanol induced sub-acute hepatotoxicity. Both ethanol and malotilate were administered for 21 days to evaluate the toxicity and prevention by the drug molecule. Methods: Thirty adult healthy Sprague Dawley rats of either sex, weighing 200-250 g selected for the study, were randomly divided into 5 groups; treated with ethanol, ethanol with vehicle carboxy methyl cellulose for malotilate solution and three different doses of malotilate having six rats in each group. All the treatments were given once a day for 21 days. On 22nd day, rats were sacrificed by cervical dislocation and dissected for collection of liver. The dissected livers were divided into two parts. One part was homogenized to assess oxidative stress marker enzymes malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) spectrophotometrically and second parts of the liver were processed for histopathological assessment i.e. histopathological scores (HPS) of liver damage. Results: Malotilate (100, 50 and 25 mg/kg) significantly reduced MDA levels and increased SOD as well as CAT levels when compared with only ethanol treated group and ethanol with vehicle for drug solution treated groups suggested antioxidant activity. The malotilate treatment groups scored the lowest HPS suggested remarkable liver protection from alcohol induced injury. Conclusions: The overall results, suggested the significant liver protection offered by malotilate by reducing oxidative stress in a dose-dependent manner. The histopathological scoring evidenced the prevention of hepatotoxicity by malotilate, which showed significant activity in 21 days of treatment. Future studies may be focussed on the molecular mechanism of the drug and its curative property as hepatoprotective action.